Determination of Employee Engagement and Employee Performance in the Hotel Sector: Analysis of Discipline and Competency (Study Literature Review) - Siska Yuli Anita; Nuraeni Nuraeni; Rita Mulyanti; Mochammad Subagio; Ahmad Faisal (Greenation International Journal of Tourism and Management, 2024)
The article determining employee engagement and employee performance in the hospitality sector: Discipline and competency analysis is a scientific literature review article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Discipline influences the involvement of hotel sector employees; 2) Competence influences the involvement of hotel sector employees; 3) Discipline influences the performance of hotel sector employees; 4) Competency influences the performance of hotel sector employees; and 5) Employee involvement influences the performance of hotel sector employees.